METHODOLOGY OF DEVELOPING PHYSICAL QUALITIES IN STUDENTS (American Journal of Pedagogical and Educational Research, 2025)
This article describes the structural basis of the development of physical qualities in relation to progressive morphological and biochemical changes in the musculoskeletal system, central and peripheral nervous systems, and internal organs, and the methodology for educating the physical qualities of high-grade students.